1971
DOI: 10.1007/bf00171974
|View full text |Cite
|
Sign up to set email alerts
|

Wave dynamics in the thermosphere: I: Tidal motion

Abstract: The atmospheric tides, their transmission and excitation in the thermosphere, are discussed in reviewing various investigations in this field. We are still fairly ignorant on the subjects and facing various unsolved problems although there is an established link between the theory and the observation in the dynamo region, the lower boundary of the thermosphere. As to the middle and upper thermosphere the observed data are scanty and only those obtained by satellite drag are available; the theoretical approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
1975
1975

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Haurwitz (1965) found that the observed diurnal barometric variation with latitude cannot be expressed by a combination of positive modes. These gave evidence for the existence of the negative mode in the atmosphere (Kato, 1971). Lindzen (1967a) discussed the thermal excitation of the diurnal and semi-diurnal tides by ozone and water vapour absorbing solar radiation.…”
Section: Classical Tidal Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Haurwitz (1965) found that the observed diurnal barometric variation with latitude cannot be expressed by a combination of positive modes. These gave evidence for the existence of the negative mode in the atmosphere (Kato, 1971). Lindzen (1967a) discussed the thermal excitation of the diurnal and semi-diurnal tides by ozone and water vapour absorbing solar radiation.…”
Section: Classical Tidal Theorymentioning
confidence: 99%
“…Further, Tarpley (1970) found a current system induced by a given horizontal velocity with diurnal first negative mode ( Figure 13) to be very similar to that deduced from the geomagnetic Sq variations such as Chapman and Bartels (1940). Maeda, K. and Kato (1966), and Kato (1971) reviewed these problems in detail.…”
Section: Ionospheric Dynamomentioning
confidence: 99%
See 3 more Smart Citations